Spatial Regression Analysis of Crime Occurrence in DKI Jakarta: Analysis of 2021 Potensi Desa Microdata - Imansari, Nadia; Chotib, Chotib (The Indonesian Journal of Planning and Development, 2024)
Urban crime is a critical issue that demands attention to support the realization of urban resilience. Urban areas with complex social conditions face an elevated risk of criminal activity. Besides economic factors, other determinants such as education and urbanization significantly contribute to urban crime. In 2021, the Special Capital Region of Jakarta recorded 20,370 criminal incidents. To gain a more comprehensive understanding of urban crime, conducting spatial analysis is essential. This study aims to perform a spatial regression analysis of crime occurrences in the province in 2021 and examine the influence of contributing factors using the 2021 Potensi Desa microdata as the primary source. The analysis encompassed 261 urban villages and employed a nomothetic explanatory quantitative approach, incorporating descriptive and inferential methods through classical and spatial regression modeling. This study finds that variables such as the urban index, education, and sports activities significantly affect the occurrence of criminal acts, although no spatial influence was observed. This study provides implications for urban planning and development by emphasizing the importance of optimizing spatial planning and human development in formulating effective strategies to address urban crime challenges.